Pengaruh Budaya Organisasi dan Kompetensi terhadap Motivasi Kerja PT. Selaras Mitra Sejahtera - Solehudin Solehudin (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2017)
This study aims to determine whether the Effect of Organizational Culture and Competence on Employee Work Motivation PT Selaras Mitra Sejahtera partially or simultaneously. This research was conducted using quantitative descriptive and verification methods, namely collecting, presenting, analyzing, and testing hypotheses, and making conclusions and suggestions. Samples were collected using Saturated Sampling method with 140 respondents from a population of 140 employees. Data collection techniques using questionnaires and observations. To see the effect, the analysis used is path analysis. So that the results of the study will be known partially variable Organizational Culture and Competence have a significant effect on Work Motivation. The research results can be concluded that there is an influence of organizational culture and competence on work motivation. And there is a simultaneous influence of Organizational Culture (X1) and Competence (X2) on Work Motivation (Y). This shows that motivation and work discipline together have an influence on the performance of employees of PT. Putra Bintang Sembada.